Leveraging Artificial Intelligence to Optimize ETL Pipelines: Enhancing Efficiency, Accuracy, and Scalability - Gaurav Naresh Mittal (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative impact of Artificial Intelligence on Extract, Transform, Load (ETL) processes in modern enterprise data management. The article examines how AI technologies enhance data extraction through intelligent discovery systems, unstructured data processing, and adaptive web scraping capabilities. It investigates the role of AI in data transformation, including automated cleansing, smart mapping, and real-time quality monitoring. The article further analyzes AI’s contribution to optimizing data loading through intelligent scheduling and adaptive performance tuning, examining self-healing capabilities and predictive maintenance in data systems. Additionally, the article evaluates how AI enables scalable and efficient infrastructure management, providing insights into resource optimization and performance enhancement strategies for enterprise data operations.